2020
DOI: 10.1136/archdischild-2019-317996
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with chronic disease and social media: a cross-sectional study

Abstract: ObjectiveThis study aims to explore the attitude of adolescents with chronic diseases toward social media exposure, focusing in particular on Facebook.DesignCross-sectional study.SettingAn anonymous semistructured survey was distributed to an Italian hospital-based cohort of adolescents with chronic disease to explore the role of Facebook in their daily life.PatientsWe recruited 212 adolescents (aged between 13 and 24 years) with a diagnosis of inflammatory bowel disease, coeliac disease, diabetes mellitus typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…One Italian study that studied patients with 4 conditions, including IBD and T1D, found that 98% expressed a need to share their medical condition on social media [ 14 ]. However, another study of patients with connective tissue disorders noted only 17% revealed their condition on social media [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Italian study that studied patients with 4 conditions, including IBD and T1D, found that 98% expressed a need to share their medical condition on social media [ 14 ]. However, another study of patients with connective tissue disorders noted only 17% revealed their condition on social media [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of private groups on Facebook helps assuage some concerns about privacy. A large number of patients used Facebook to search for friends with the same disease or community support groups to find others who were going through the same thing and could understand their feelings [ 14 ]. These online social connections might be particularly important for patients with IBD as some researchers have postulated that the embarrassment of frequent bathroom trips or diarrhea might lead to perceived stigma and social withdrawal [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of intense virtual activity, which facilitated relationships, could reproduce some dynamics of conflict and competition among peers, explaining the similar proportion of adolescent with stable relationship with peers between the two groups [ 18 ]. Finally, a different role of social media use could be postulated due to its relevant role in adolescents with chronic illness [ 19 ] . It can be assumed that children with SSD were more comfortable during isolation in the context of remote school lessons and more intense use of social media than peers with a different lifestyle, more focused on outdoor activities and face-to-face relationships, thus explaining the higher proportion of patients having improved their relationships with peers.…”
Section: Discussionmentioning
confidence: 99%
“…However, missing from the discussion is whether AYA with IBD also experience loneliness. Loneliness is an important issue raised by adolescents with chronic diseases [17], and meta-analytic findings show that AYA with medical conditions are vulnerable to loneliness [18,19]: AYA talk about feelings of disconnection from peers, that such disconnection impacts their quality of life, and is part of their poor mental health. To date, however, there has been no published work on loneliness among AYA with IBD.…”
Section: Ibd and Mental Healthmentioning
confidence: 99%